The evaluation and control of acoustical standing waves - Krasnegor, Norman A. (1974)
Calibration of a standard pigeon box subsequently modified for use as an acoustical chamber in a frequency discrimination experiment revealed that the enclosure was not acoustically “flat”. Standing waves were detected at each of the six frequencies measured. To ascertain whether the maximum standing waves recorded (3.0 dB) could serve as an added or alternative cue for pigeons tested in the chamber on a frequency discrimination problem, pure-tone intensity difference thresholds were determined for two pigeons at 1.0, 2.0, and 3.0 KHz. The results of the experiment indicated that the smallest intensity difference detectable was 10.0 dB, a value that was 7.0 dB above the maximum standing wave measured in the box. These data suggest that the modified pigeon chamber is suitable to test pure-tone frequency discriminations in pigeons in the range of 1.0 to 3.0 KHz.